2022
DOI: 10.1093/ofid/ofac492.449
|View full text |Cite
|
Sign up to set email alerts
|

371. Adding sputum and saliva to nasopharyngeal swab samples for PCR detection of Respiratory Syncytial Virus in adults hospitalized with acute respiratory illness may double case detection

Abstract: Background In hospitalized patients, nasopharyngeal (NP) swabs are the most common samples obtained for Respiratory Syncytial Virus (RSV) PCR testing. However, adding sputum is known to increase diagnostic yield, and saliva has been successfully used for viral respiratory infection diagnosis. We sought to compare RSV prevalence detected by PCR testing of NP swab alone versus NP swab plus saliva and sputum in adult patients hospitalized with acute respiratory illness (ARI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…We assumed that a combination of sputum, saliva, and nasopharyngeal specimens testing through PCR plus paired serology would be the gold standard. The detection proportion was calculated on the basis of a prospective multi-specimen study that found a 1.6-fold increase in RSV detection adding saliva and sputum specimens to nasopharyngeal swab [ 18 ]. For both steps, we incorporated the innate statistical uncertainty around the testing accuracy studies through a Bayesian approach and sampled 1000 times from the posterior beta distribution of detection proportion based on data and assumed non-informative prior distribution (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that a combination of sputum, saliva, and nasopharyngeal specimens testing through PCR plus paired serology would be the gold standard. The detection proportion was calculated on the basis of a prospective multi-specimen study that found a 1.6-fold increase in RSV detection adding saliva and sputum specimens to nasopharyngeal swab [ 18 ]. For both steps, we incorporated the innate statistical uncertainty around the testing accuracy studies through a Bayesian approach and sampled 1000 times from the posterior beta distribution of detection proportion based on data and assumed non-informative prior distribution (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…rapid antigen test), which could also be used for adjusting for case under-ascertainment [ 12 ]; the adjustment did not consider the diagnostic value of a third (or more) diagnostic test or specimen, in addition to paired serology and sputum. Moreover, no studies have evaluated the benefit of adding saliva, which has been shown to be a sensitive specimen type for viral respiratory testing [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults often show diminished viral presence, especially if tested late, and generally have lower viral concentrations than children [44]. Broadening testing to include saliva, sputum, and serology have proven more effective [10 ▪▪ ]. A recent study in US has shown that RSV prevalence by nasopharyngeal swab alone was 1.8% but increased to 4.5% when saliva (and sputum) was added [10 ▪▪ ].…”
Section: Challenges To Identifying Morbidity Burden In Older Adultsmentioning
confidence: 99%
“…Broadening testing to include saliva, sputum, and serology have proven more effective [10 ▪▪ ]. A recent study in US has shown that RSV prevalence by nasopharyngeal swab alone was 1.8% but increased to 4.5% when saliva (and sputum) was added [10 ▪▪ ]. These data were utilized in the recent meta-analysis by Li et al [8 ▪▪ ] to report that the annual estimates RSV hospitalizations in adults ≥65 years industrialized countries could be as high as 787 000 (460–1347).…”
Section: Challenges To Identifying Morbidity Burden In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation